Return to Recreational Sporting Activities Following Total Shoulder Arthroplasty. Issue 7 (21st July 2017) - Mannava, Sandeep; Horan, Marilee P.; Frangiamore, Salvatore Joseph; Fritz, Erik M.; Godin, Jonathan Alexander; Pogorzelski, Jonas; Millett, Peter J.
Objectives: Total shoulder arthroplasty (TSA) is a surgery performed for end-stage shoulder pain and degeneration. Many patients who undergo TSA are limited in their ability to participate in recreational sporting activities secondary to their shoulder dysfunction. The purpose of this study is to examine the ability of patients to return to recreational sport following TSA. We hypothesize that TSA will allow for return to pre-surgical recreational sport following the arthroplasty procedure. Methods: A total of 170 patients who underwent primary TSA by the senior author and indicated they participated in recreational sporting activities met the inclusion criteria and were studied for their ability to return to their recreational activity following surgery. A minimum of 2-years of follow up was required for inclusion in the study. Additionally, ASES, QuickDASH, SANE, SF-12 PCS, and median patient satisfaction on a scale of 1-10 (with 10 being totally satisfied) was compared preoperatively to postoperatively. Patients were excluded from analysis if they were undergoing a revision arthroplasty procedure or indicated they did not participate in recreational sporting activity. Statistical analyses were performed using statistical software SPSS version 11.0 (SPSS, Chicago, IL). Results: A total of 170 patients met inclusion criteria for the study with a mean age of 63.7 years old (range 18-82). A total of n=12 patients required additional surgical intervention after the index TSA procedure, n=8 required lysis of adhesions/debridement and n=4 required revision from TSA to reverse TSA. A total of 131 of the 170 patients more specifically participated in recreational activities. Activities included golf (n=33), tennis (n=14); biking (n=12); swimming (n=5); weight lifting (n=11); snow sports (n=25); and other sports (n=32 including: wrestling, walking, hiking, fishing, throwing, softball, soccer, running, sailing, rancher/farmer, hunting, horseback riding, kayaking, rafting). The type of recreational activity did not make a difference in outcome scores. There was a significant increase preoperatively to postoperatively in the mean ASES (48.5 to 85.9, p<0.05); Quick DASH (40.0 to 16.2, p<0.05); SANE (49.8 to 80.2, p<0.05); SF-12 PCS (57.5 to 48.4, p<0.05); and median satisfaction after surgery was 10. The rate of return to pre-surgical recreational sporting activity following TSA was 69.7%. 24% reported some difficulty and 6.4% reported very difficult or unable to return to recreational activity. Conclusion: Patients undergoing TSA improve from their pre-operative functional level as assessed by their significant improvement in their outcome scores and satisfaction. Additionally, patients who indicated that they participate in recreational sporting activities were able to successfully return to their pre-surgical recreational activities. Patients undergoing TSA can be counseled that they can expect to successfully return to sporting and recreational activities following surgical reconstruction of their shoulder.